Derivatives Markets - McDonald, Robert L. (Pearson Education, 2013)
For courses in options, futures, and derivatives. To be financially literate in today's market, business students must have a solid understanding of derivatives concepts and instruments and the uses of those instruments in corporations. The Third Edition has an accessible mathematical presentation, and more importantly, helps students gain intuition by linking theories and concepts together with an engaging narrative that emphasizes the core economic principles underlying the pricing and uses of derivatives. The third edition has been updated to include new data and examples throughout.